Capacity Building for Internationalization at a Technical University in Kazakhstan - Damira Jantassova; Daniel Churchill; Aigerim Kozhanbergenova; Olga Shebalina (MDPI AG, 2021)
This article discusses the internationalization capacity building project at the Karaganda Technical University ('KTU') in Kazakhstan. The project, entitled "Capacity building for the internationalization of a technical university by means of digital learning technologies," was supported by the fund "Scientific foundations "Mangilik el" (education of the 21st century, fundamental and applied research in the humanities)" for scientists 2020-2022. The project's primary purpose was to explicate a sustainable strategy for internationalizing a Kazakh technical university, considering the national and international contexts, evaluating internationalization capacity needs, formulating and implementing a capacity-building response for internationalization, and enhancing the qualifications and abilities of students and teachers to an internationally comparable level. In addition, the project delivers a set of strategies for internationalization and a benchmarking methodology for evaluating the effectiveness of internationalization processes. The benchmarking analysis of the internationalization process of a university has been conducted through a classification method, comparative analysis, multi-factor SWOT analysis, and correlation analysis.